PENGARUH TERAPI REBUSAN DAUN KERSEN TERHADAP PENURUNAN KADAR GULA DARAH PADA PENDERITA DIABETES MELITUS PADA MASYARAKAT DI PUSKESMAS SA’DAN MALIMBONG KABUPATEN TORAJA UTARA TAHUN 2023 - Algarini Allo, Olgrid; Patabang, Meri (Institut Toraja Raya Indonesia (ITRI), 2023)
Kersen leaf decoction therapy is one of the traditional ingredients used to treat diabetes mellitus because it has active anti-diabetic substances, namely corbic acid, fiber, niacin and beta carotene. The aim of this research is to determine the effect of cherry leaf decoction therapy on reducing blood sugar levels in people with diabetes mellitus at the Sa'dan Malimbong Community Health Center, Sa'dan District, North Toraja Regency in 2023. This type of research is a quasi-experiment. The population in this study were diabetes mellitus sufferers in the Sa'dan Malimbong health center working area. The sample size was 10 respondents using a purposive sampling technique. Data collection was carried out using the results of GDS measurements of diabetes mellitus sufferers. Data analysis was carried out with the help of SPSS version 25 using the Wilcoxon test with a significance level of p < 0.05. The results of the research were obtained after administering cherry leaf decoction therapy, most of the characteristics aged 30-45 and 66-75 years each were 2 people (20.0%), 46-65 as many as 6 people (60.0%) respondents had Normal GDS scores were 7 people (70.0%), while respondents with high GDS scores were 3 people (30.0%). The statistical test results obtained a significance value of p= 0.008 (p<0.05). The conclusion of this research is that there is an effect of cherry leaf decoction therapy on reducing blood sugar levels in people with diabetes mellitus in the Sa'dan Malimbong Community Health Center, Sa'dan District, North Toraja Regency in 2023. It is hoped that consuming cherry leaf decoction will control GDS for diabetes mellitus sufferers.